2003
DOI: 10.5507/bp.2003.004
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Prosthesis-Related Infection

Abstract: In spite of its incidence decreasing to 1% nowadays, prosthesis-related infection remains a research, diagnostic, therapeutic and cost-related problem. It can be defined as a presence of bacteria in the artificial joint space, which is significantly associated with evident laboratory and/or tissue markers, and clinical signs of running infection. We believe that the more precise understanding of pathogenesis, the more effective preventative and therapeutic measures, and the lower infection rate. The implants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 69 publications
0
45
1
4
Order By: Relevance
“…However, that level may be an underestimation, because it has been shown that detection of polymicrobial growth increases from up to 20% by conventional culture methods to 63% by extensive microbiological culture from an explanted prosthesis (Neut et al 2003, Lentino 2004. As proposed by Gallo et al (2003), a symbiotic relationship between several bacterial species may be advantageous for the development of biofilms. A surgical site infection after primary or revision hip replacement is a risk factor for development of a deep prosthesis infection (Wymenga et al 1992), which is supported by our data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, that level may be an underestimation, because it has been shown that detection of polymicrobial growth increases from up to 20% by conventional culture methods to 63% by extensive microbiological culture from an explanted prosthesis (Neut et al 2003, Lentino 2004. As proposed by Gallo et al (2003), a symbiotic relationship between several bacterial species may be advantageous for the development of biofilms. A surgical site infection after primary or revision hip replacement is a risk factor for development of a deep prosthesis infection (Wymenga et al 1992), which is supported by our data.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known how long an occult bacterial infection on the surface of a prosthesis can last without provoking a host response, although a period of several years seems possible (Nguyen et al 2002, Tunney et al 1998, during which the process of periprosthetic osteolysis might maintain immunoincompetence-and also facilitate expansion of biofilm growth (Gallo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implants may be colonized by airborne, skin, and/or surgeon-related bacteria during surgery despite use of closely monitored surgical techniques. After successful attachment on the biomaterial surface, bacteria multiply and form a "biofilm" community, which makes them much more resistant to antibiotic therapy and host immunity [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the indolent and shifty nature of late occurring infections is more typical of less virulent bacteria such as coagulase-negative staphylococci. 3 Various algorithms have been proposed to improve joint sepsis diagnostics, including clinical, serological, microbiological, and imaging techniques. 4 It has been suggested that one useful method for lowgrade prosthetic sepsis bacteria identification should be sensitive and specific enough to allow early and adequate therapy.…”
Section: Introductionmentioning
confidence: 99%